Variation of main components according to the number of steaming and drying of Rehmanniae radix preparata - Ui Joung Youn; Bon-Seok Gu; Kyung Hee Kim; Chulgyu Ha; In Chan Jung (Korean Pharmacopuncture Institute, 2018)
Contents of compounds in Rehmanniae Radix change depending on the number of steaming and drying and the drying method. In this study, as an impregnation method for dried Rehmanniae Radix, takju impregnation and cheongju impregnation were carried out and steaming and drying were repeated for 9 times. The changes of 5-HMF and catalpol contents were analyzed according to the number of repetition times to investigate which stage of steaming and drying is preferable. Also, total nitrogen, crude fat, ash, and crude fiber were measured to analyze changes in general components. 5-HMF was not detected in dried Rehmanniae Radix. As a result of repetitive steaming and drying, the content of 5-HMF increased only slightly from 1 to 4-times steaming and drying but increased significantly from 5-times. The catalpol in dried Rehmanniae Radix was not detected after 5 times of steaming and drying. Sucrose, maltose, and glucose were included in dried Rehmanniae Radix before steaming and drying. However, after the process in both Takju impregnation and Cheongju impregnation, galactose and fructose tended to decrease after production and sucrose and glucose tended to decrease after the increase. In this study condition, 6-times and more steaming and drying were appropriate process which met the content criteria (not less than 0.1%) of the Korean Pharmacopoeia (8th edition) for 5-HMF, an index component for quality control of Rehmanniae Radix Preparata.